The Impact of Taxes on the Performance of Micro Enterprises: A Case Study of Nsuube-Buguju Parish Mukono TC Division - Emmanuel Owoko (Uganda Christian University, 2024)
The study went out to investigate the impact of taxes on the performance of Micro Enterprises in Nsuube-Buguju Parish, Mukono TC Division. The study flowed following these three objectives: the relationship between tax rates and the performance of Micro-enterprises, secondly, the relationship between tax incentives and the performance of Micro Enterprises and lastly, the relationship between tax compliance and the performance of Micro Enterprises in Buguju. The study was carried out using explanatory research design where quantitative research approach was utilized. Stratified sampling method and purposive sampling method was used to get a sample of 80 respondents who were Micro Enterprises owners and managers of the selected businesses dealing in segmented businesses and assorted merchandize in Buguju village, and these responded to the questionnaires that were used to collect data. The study found that tax policies have a big influence on the growth and sustainability of micro enterprises. It is also encouraging to see that most respondents concurred that the tax rates were explicitly stated and that the organizations running the Micro-enterprises were aware of the tax payment procedures. However, it raises issues with the perception that taxes are unsupportable by many Micro Enterprise owners, primarily because they are regressive, which has an impact on the bases from which revenues are drawn. In addition, the region's micro enterprises' capacity to grow and flourish is hampered by the apparent lack of tax incentives for them. Therefore, tax compliance is essential to Micro Enterprises' success. In fact, there is a positive association between the performance of Micro Enterprises and their owners' consistent timely filing of returns, payment of taxes, and adherence to tax legislation. In the end, it produced a lengthy list of suggestions aimed at promoting and reducing the tax burden on micro-enterprises. These included streamlining tax laws, developing targeted tax incentives, enhancing tax education initiatives, changing regressive tax laws, fostering greater collaboration between tax authorities and micro-enterprises, offering regular policy reviews, and even appointing a tax ombudsman specifically for micro-enterprises. By lowering taxes, offering incentives, educating Microenterprises, and promoting collaboration, policymakers can further foster this atmosphere and help these businesses grow, innovate, and comply with regulations thereby addressing some of their very particular problems.